Answer:
81
Step-by-step explanation:
![{x}^{2} + 18x + {(( \frac{1}{2})(18)) }^{2}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%2018x%20%2B%20%7B%28%28%20%5Cfrac%7B1%7D%7B2%7D%29%2818%29%29%20%7D%5E%7B2%7D%20)
![{x}^{2} + 18x + {9}^{2}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%2018x%20%2B%20%20%7B9%7D%5E%7B2%7D%20)
![{x}^{2} + 18x + 81](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%2018x%20%2B%2081)
![{(x + 9)}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20%2B%209%29%7D%5E%7B2%7D%20)
Here is my work for the problem. Hope this helps!
The given mathematical expression <span>2 (c+7)=2c+14 is an example is</span> an example of Distributive Property.
We can examine the given problem, we have 2(c+7) where 2 can be distributed to both c and 7. Then the result of distribution is 2c and 14 which the same in the opposite side.
Answer:
Vamos a resolver la ecuación paso a paso.
32x+4=642x−1
Step-by-step explanation:
Resolver el exponente.
32x+4=642x−1
log(32x+4)=log(642x−1)(Sacar el logaritmo de ambos lados.)
(x+4)*(log(32))=(2x−1)*(log(64))
x+4=(
log(64)
log(32)
)*(2x−1)
x+4=1.2*(2x−1)
x+4=2.4x−1.2(Simplificar ambos lados de la ecuación)
x+4−2.4x=2.4x−1.2−2.4x(Restar 2.4x a ambos lados)
−1.4x+4=−1.2
−1.4x+4−4=−1.2−4(Restar 4 a ambos lados)
−1.4x=−5.2
−1.4x
−1.4
=
−5.2
−1.4
(Dividir ambos lados por -1.4)
x=3.714286
Solución:
x=3.714286